ANALYSIS OF RISK MANAGEMENT IN BUILDING WORKERS OF SMAN 5 BRAWIJAYA BUILDING KEDIRI - Setiawan, Endik; Witjaksana, Budi; TJendani, Hanie Teki (Transpublika Publisher, 2023)
Construction projects are a job sector that has level risks and work accident , this is caused consequence low awareness to application Occupational Safety and Health (K3) and in accordance with the regulations applicable legislation. Often application of K3 to a construction project considered only as a cost expense , not as an investment to prevent happen work accidents but can give level loss of the construction project. Kediri is city biggest third in East Java province after Surabaya and Malang according to population . Kediri City is city the oldest in East Java. SMAN 5 Taruna Brawijaya Kediri, East Java was built with the aim of support teaching and learning activities. Results of the analysis it can be categorized Work accidents among construction workers at SMAN 5 Brawijaya Kediri : Indiscipline workforce , Do not have standardization of good and clear K3 implementation, Refuse recommendation use of personal safety equipment , No evaluation system regarding the implementation of work in implementing K3, and unclear division of tasks in formation organization so it is not clear how to implement it.